Modyfikacja algorytmu Changa z wykorzystaniem metody znajdowania punktów najbliższych - Sierszeń, Artur (Wydawnictwa AGH, 2007)
The modification of Chang's algorithm consisting in replacement of the original method of determining the distance to the nearest point from the same class with modified methods of finding the mutually nearest points causes a great acceleration of the computational phase. Results of experiments show that the presented method does not significantly decrease the quality of classification.

Modyfikacja algorytmu Changa polegająca na zastąpieniu oryginalnego sposobu wyznaczania odległości do najbliżej położonego punktu z tej samej klasy zmodyfikowanymi metodami znajdowania punktów najbliższych przynosi dużą akceleracje obliczeń. Przeprowadzone eksperymenty dowodzą, że zaproponowana metoda nie zmniejsza w sposób istotny jakości klasyfikacji.
Modification of Chang's algorithm with the method of finding the mutually nearest points
Automatyka
Keywords: pattern recognition; modification of Changs algorithm; changs algorithm; acceleration of the computational phase; k-NN rules; rozpoznawanie obrazów; modyfikacja algorytmu Changa; set Glass; akceleracja obliczeń; reguła k-NN; set Iris; algorytm Changa; zbiór Glass; set Ima; zbiór Iris; zbiór Pima; set Wine; zbiór Wine